2021
DOI: 10.9734/jpri/2020/v32i4831125
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Virus Types 16/18 Distribution in Invasive Cervical Cancer: An Evidence for Vaccination in Bihar, India

Abstract: There is high incidence of cervical cancer in Bihar, India. Vaccination for cervical cancer in developed countries has played a crucial role in limiting the incidence rate of cervical cancer worldwide. In consideration of debate on clinical efficacy of Human Papilloma Virus (HPV) vaccine in India, study on the prevalence of high risk HPV 16/18 strains in different regions of the nation becomes very crucial. Few individual states have started vaccination but centralised vaccination program does not exist due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…A similar study reported HPV prevalence statistics in agreement with our observations that HPV16 constituted the majority (79.37%) of HPV infections followed by HPV18, 33, 31, and 45 [12]. HPV prevalence data aligning with our findings was observed in a study performed by Kumar et al, who reported a prevalence of HPV16 (77.08%) and HPV18 (16.67%) [13]. Additionally, consistent with our findings, the prevalence of 66.7% for HPV16 and 19.4% for HPV18 was reported from Andhra Pradesh [11].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A similar study reported HPV prevalence statistics in agreement with our observations that HPV16 constituted the majority (79.37%) of HPV infections followed by HPV18, 33, 31, and 45 [12]. HPV prevalence data aligning with our findings was observed in a study performed by Kumar et al, who reported a prevalence of HPV16 (77.08%) and HPV18 (16.67%) [13]. Additionally, consistent with our findings, the prevalence of 66.7% for HPV16 and 19.4% for HPV18 was reported from Andhra Pradesh [11].…”
Section: Discussionsupporting
confidence: 93%
“…Pan-India, HPV occurrence of type 16 alone is reported to be 70-90% and HPV18 prevalence generally varies from 3% to 20% [3][4][5][6][11][12][13]. In this study, while categorizing and quantifying the prevalent viral genotypes of HR-HPV, HPV16 emerged as the most prevalent type (68.65%) whereas the prevalence of HPV18 was 24.62%.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations